Deletion of Chromosome 4q Predicts Outcome in Stage II Colon Cancer Patients - R. P. M. Brosens; E. J. T. H. Belt; J. C. Haan; T. E. Buffart; B. Carvalho; H. Grabsch; P. Quirke; M. A. Cuesta; A. F. Engel; B. Ylstra; G. A. Meijer (Analytical Cellular Pathology)
Background: Around 30% of all stage II colon cancer patients will relapse and die of their disease. At present no objective parameters to identify high-risk stage II colon cancer patients, who will benefit from adjuvant chemotherapy, have been established. With traditional histopathological features definition of high-risk stage II colon cancer patients is inaccurate. Therefore more objective and robust markers for prediction of relapse are needed. DNA copy number aberrations have proven to be robust prognostic markers, but have not yet been investigated for this specific group of patients. The aim of the present study was to identify chromosomal aberrations that can predict relapse of tumor in patients with stage II colon cancer.